(untitled) (Proceedings of the European Wave and Tidal Energy Conference, 2023)
Assessment of the upstream flow available to the tidal energy converters (TEC) is key to evaluate its performance. Simultaneously, TEC technology has been innovating on its concepts and designs to expand the potential sites to harvest energy generated by tidal currents and rivers. The Gkinetic CEFA 12 is an easy-to-deploy device suitable to operate on estuary environments. The design consists of two 1.2 m vertical axis turbines attached to the sides of a buoyant platform, which uses a bluff body to accelerate the incoming flow to the rotors. The device was deployed on a single point mooring enabling passive flow alignment. As part of the Vertical axis tidal turbines in Strangford lough project (VATTS), the upstream flow has been measured using acoustic doppler profilers (ADP) mounted on the TEC during its operation in Strangford lough. Recommendations of IEC-200 were followed when mounting the ADPs relative to Gkinetic. However, the continuous repositioning of the TEC according to the prevailing tidal regime affects the ADPs heading. The implications of the spatial variation of the rotor’s upstream velocity on the resource assessment and device performance are not clear since this situation is not typical. To investigate the spatial variation of the upstream velocity two ADCP deployment locations were made. A seabed (upward facing) ADCP as per the current standards and a device mounted (downward facing) ADCP upstream of the rotor plane. Evaluation of the influence of the following three factors were made: i) the ADPs direction repositioning according to prevailing tidal regime, ii) the proximity of the sensors to the sea-surface, and iii) the proximity of the sensors to the TEC. These three factors will be evaluated using ADP datasets collected at Strangford narrows during the VATTS project. The datasets were obtained at approximately the same location of the TEC operation. They enable the study of the following scenarios 1) incoming flow to the rotors during operation, 2) incoming flow on undisturbed conditions (no turbine operation), and 3) a harmonic analysis prediction of the undisturbed incoming flow, which solely captures the tidal-driven flow. The investigation of these three scenarios will provide a better understanding on the rotor’s upstream flow spatial variation, and the influence of the device’s proximity and near sea surface conditions on the mean flow. These findings would benefit developers of alternative TEC designs that operate near the sea-surface.